1D Organic–Inorganic Hybrid Perovskite Micro/Nanocrystals: Fabrication, Assembly, and Optoelectronic Applications. Issue 7 (10th April 2018) - Xu, Xiuzhen; Zhang, Xiujuan; Deng, Wei; Jie, Jiansheng; Zhang, Xiaohong
Abstract: 1D perovskite micro/nanocrystals (1D PMCs) have captured the interest of scientists because they have fascinating properties and many potential technological applications. In comparison to polycrystalline perovskite films, 1D PMCs with well‐defined crystal structures possess larger carrier mobilities, higher photoluminescence quantum yields, and longer carrier diffusion lengths, making them an attractive system for both fundamental research and device applications. Here, recent developments in the controllable fabrication of 1D PMCs with excellent optoelectronic properties are described. Special attention is paid to methods for the aligned/patterned assembly of 1D PMCs, including evaporation‐induced self‐assembly, meniscus‐assisted self‐assembly, confinement self‐assembly, and template‐guided self‐assembly methods. Recent progress in the use of 1D PMCs in photodetectors, lasers, light‐emitting diodes, and solar cells is also reviewed. Finally, the challenges and outlook of 1D PMCs in future device applications are presented. Abstract : Recent advances in controllable fabrication, large‐scale assembly, and optoelectronic applications of 1D organic–inorganic hybrid perovskite micro/nanocrystals (1D PMCs) are highlighted. The future directions and challenges of the 1D PMCs are also presented.